ANALYSIS OF THE POSITIONING OF SUPERMARKETS THROUGH A MULTIDIMENSIONAL SCALE IN PERCEPTUAL MAPS - Pazmiño Garzón, Denise Liliana; Hidalgo Pumagualle, Esteban Josué; Gavilánez Álvarez, Oscar Danilo; Granizo Espinoza, Ximena Patricia (mktDESCUBRE, 2020)
The main objective of this research work is to determine the level of positioning of supermarkets in Riobamba city, based on the perception of the city’s target audience. The study approach is quantitative, descriptive research is used and the inductive method is applied. The analyzed attributes considered in the survey were: product assortment and price, the same ones that were determined through a validation of variables. Its evaluation was carried out using a semantic differential scale because it facilitates expressing the magnitudes of the attributes in numerical values. From the results obtained, a perceptual map of multidimensional scale positioning is constructed, which specifies from the point of view of the consumer the differential benefits offered by each of the supermarkets, while from the point of view of the company, allows to know what position the company occupies in the mind of the consumer in relation to the competition. The findings of this study provide valuable information to retailers of mass consumption, encouraging them to develop competitive strategies that are focused on the final consumer.